Development Of Reduced Calorie Chocolate Cake With Jackfruit Seed (Artocarpus Heterophyllus LAM.) Flour And Polydextrose Using Response Surface Methodology (RSM) Programmed - Amin, Siti Faridah Mohd (2009)
Reduced calorie cake was developed from response surface methodology (RSM) programmed by replacing sucrose with 11% polydextrose and wheat flour with 16% jackfruit seed flour (JFSF). Proximate analyses indicated that reduced calorie cake was high in moisture (31.17%), crude fibre (5.02%) dan protein (9.89%) but low in fat (3.52%) content. In physical analyses, reduced calorie cake has higher symmetry index (2.20) as compared to the control cake (1.40) but showed no different in specific volume and uniformity. It has lower calorie value (251 kcal/100g) as compared to control cake (379 kcal/100g).